Public Perception Of Taxation Obligations And Its Effect On Tax Compliance In Indonesia - Susena , Karona Cahya; Fitriani, Asty Eka; Hidayah , Nenden Restu; Wijaya, Ermy (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2025)
This article discusses how public perception of tax obligations can affect the level of tax compliance. Positive perceptions of taxes have the potential to encourage higher levels of compliance, which in turn will ensure sufficient state revenues and increase legitimacy and trust in the government. Conversely, negative perceptions can lead to low tax compliance. There are many factors that influence how the public views tax obligations, including social, economic, legal, cultural values, education, wealth distribution, and tax law policies and transparency. All of these factors play a role in shaping public behavior and views on taxes. This article uses the Systematic Literature Review (SLR) method, where relevant literature is collected, reviewed, and analyzed to obtain comprehensive conclusions. Based on the results of the literature search, it is known that public perception of tax obligations in Indonesia generally shows a positive tendency, with increasing awareness and positive sentiment towards taxes. However, the major challenge faced is the low level of tax compliance, which is caused by a lack of understanding, less than optimal services, and low trust in the government. Therefore, government efforts to improve tax education, improve service quality, and build public trust are very important in order to improve tax compliance in the future.